Socio-economic Status and Demographic Profile of Totapuri Goat Keepers in North-Eastern Rajasthan - Meena, Sunil Kumar; Nagda, Rajendra Kumar; Gautam, Lokesh; Mishra, Renuka; Gurjar, Mittha Lal; Meel, Mahendar Singh; Purohit, Kamal (International Journal of Bio-resource and Stress Management, 2025)
The present study was conducted during June 2023 to August 2024 at the Department of Animal Genetics and Breeding, College of Veterinary and Animal Science, Navania, RAJUVAS, Rajasthan, India to study the socio-economic status and demographic profile of Totapuri goat keepers in north-eastern Rajasthan. Based on an extensive analysis of a dataset comprising a total of 3080 goats across three districts in Rajasthan, this study presents significant findings pertaining to the socio-economic and demographic profile of Totapuri goat farmers. The analysis revealed a predominance of middle-aged individuals (41–60 years) within the goat rearing community across all three regions. Specifically, the distribution of respondents was 29.47% for younger individuals (under 40 years). The research also highlighted that the Scheduled Tribes (ST) category constituted the majority, particularly in Alwar and Dausa, constituting 70.53% of the studied region, while Karauli showed a substantial percentage of Most Backward Classes (MBC) at 34.61%. Furthermore, 90.52% of respondents were engaged in a combination of agriculture and animal husbandry in all the districts, underscoring the integrated nature of their livelihood activities. The housing situation indicated a relatively prosperous economic status among Totapuri goat keepers, as the majority lived in pucca houses. Additionally, a significant average family size of 7.75 members was observed, with variations across regions. Based on these findings, it can be concluded that goat farming, particularly of the Totapuri breed, plays a crucial role in sustaining the livelihoods of farm owners in the examined districts, with evident implications for rural economic development.